Stoichiometric optimization of Gata4, Hand2, Mef2c, and Tbx5 expression for contractile cardiomyocyte reprogramming - Zhang, Zhentao (Sci Rep, 2019)
Reprogramming of fibroblasts to induced cardiomyocyte-like cells (iCMs) offers potential strategies for new cardiomyocyte generation. However, a major challenge of this approach remains its low efficiency for contractile iCMs. Here, we showed that controlled stoichiometric expression of Gata4 (G), Hand2 (H), Mef2c (M), and Tbx5 (T) significantly enhanced contractile cardiomyocyte reprogramming over previously defined stoichiometric expression of GMT or uncontrolled expression of GHMT. We generated quad-cistronic vectors expressing distinct relative protein levels of GHMT within the context of a previously defined splicing order of M-G-T with high Mef2c level. Transduction of the quad-cistronic vector with a splicing order of M-G-T-H (referred to as M-G-T-H) inducing relatively low Hand2 and high Mef2c protein levels not only increased sarcomeric protein induction, but also markedly promoted the development of contractile structures and functions in fibroblasts. The expressed Gata4 and Tbx5 protein levels by M-G-T-H transduction were relatively higher than those by transductions of other quad-cistronic vectors, but lower than those by previously defined M-G-T tri-cistronic vector transduction. Taken together, our results demonstrate the stoichiometric requirement of GHMT expression for structural and functional progresses of cardiomyocyte reprogramming and provide a new basic tool-set for future studies.